DETERMINATION OF MERCURY CONTENT IN FISH PRODUCTS (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
The content of mercury in the main types of fish samples, which are reproduced in RA and in imported frozen ocean fish and in samples of canned fish, was determined. It has been shown that the content of mercury in imported fish samples is higher than in samples, which are reproduced in RA.
Keywords: content of mercury; fish samples